Development of a Triplex Real-Time PCR Method for the Simultaneous Detection of Porcine Circovirus 2, 3, and 4 in China Between 2023 and 2024 - Yanhong Chen; Yi Lu; Dongfan Li; Ling Dong; Yang Zeng; Zhijing Mei; Ahmed H. Ghonaim; USAMA; Zhixian Yu; Shuo Zhang; Ping Bai; Wentao Li; et al. (Viruses, 2025)
Background: Porcine circovirus disease (PCVD), caused by porcine circovirus (PCV), is a significant swine disease characterized by porcine dermatitis, nephrotic syndrome, and reproductive disorders in sows. Given the overlapping clinical presentations of PCV2, PCV3, and PCV4, a rapid and accurate method for their differential detection is essential. Methods: In this study, specific primers and probes were designed based on the conserved regions of the ORF1 genes of PCV2 and PCV4, as well as the ORF2 gene of PCV3. Results: A TaqMan triple real-time PCR method was developed, demonstrating excellent specificity, sensitivity, and repeatability, with limits of detection (LODs) of 53.3 copies/µL, 12.0 copies/µL, and 13.8 copies/µL for PCV2, PCV3, and PCV4, respectively. Using this method, 500 clinical porcine tissue samples collected from 23 provinces across China between 2023 and 2024 were analyzed. The results showed detection rates of 75.20% (376/500) for PCV2, 17.60% (88/500) for PCV3, and 4.40% (22/500) for PCV4. The detection rate of triple coinfections involving PCV2, PCV3, and PCV4 was 0.80% (4/500). PCV2 consistently presented significantly higher positive detection rates across all growth stages, and its viral copy number was significantly greater than those of PCV3 and PCV4 (* p < 0.05). Forty PCV2 ORF2 genes, fourteen PCV3 ORF2 genes, and three PCV4 ORF2 genes were identified. These included four PCV2a genotypes, thirty-five PCV2d genotypes, and one PCV2e genotypes; two PCV3a genotypes and six each of PCV3b and PCV3c genotypes; and two PCV4a genotypes and one of PCV4b genotype. Conclusions: The triple qPCR method established in this study provides a rapid, specific, and accurate approach for the detection and differentiation of PCV2, PCV3, and PCV4 genotypes.